OPTIMIZING USE OF ONLINE MARKETPLACE TIKTOK FOR MIGRANT MSMES IN PENANG, MALAYSIA - Rahmani, Shinta; Rifqi, Muhammad (Bajang Institute, 2025)
Indonesian migrant workers in Malaysia, particularly those running Micro, Small, and Medium Enterprises (MSMEs), face significant challenges such as struggling with inadequate living conditions, limited access to healthcare, and legal protection issues. The urgency of this activity is to address the challenges faced by MSMEs owned by Indonesian migrant workers. These predominantly micro and small businesses struggle with limited resources, manual or traditional marketing methods, and a lack of knowledge about online marketing. This hinders their ability to access a wider market, leading to decreased competitiveness and market reach. The main objectives of this community service initiative are: (1) To improve the digital marketing skills of MSME owners to increase their market reach and competitiveness. (2) To align with the Merdeka Belajar Kampus Merdeka (MBKM) program, which aims to encourage collaboration between academia and the community, and improve the quality of public services. (3) To support the Merdeka Belajar Kampus Merdeka (MBKM) program by improving public services, as indicated by Key Performance Indicators (KPIs). The population involved in this activity is Indonesia migrant workers in Penang, Malaysia who run micro, small, and medium enterprises (MSMEs). The results of this activity include: (a) Improved skills in social media marketing, particularly content creation and data analysis on TikTok. (b) Increased sales and market visibility. (c) Documentation.